Pengaruh Penggunaan Media Video Pada Pembelajaran Berbasis Masalah dan Kemampuan Awal Terhadap Hasil Belajar Siswa SMAN - Ade Wartono; Mustaji Mustaji; Suhari Suhari (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2024)
The application of problem-based learning models in its application requires the support of appropriate learning media. One of the most effective learning media is video. In addition, the factor of students' initial ability greatly affects the achievement of optimal learning outcomes. Therefore, this study aims to determine the effect of the use of video learning media and students' initial abilities on learning outcomes as well as the effect of the interaction between the two factors on student learning outcomes. The research was conducted at SMAN 2 Batu and SMAN 3 Batu on Biology subject matter of Excretory System. The results showed that There is an interaction effect of problem-based learning using video media and initial ability on learning outcomes. There were differences in Biology learning outcomes in students who participated in problem-based learning using video media and those who used torso media. Students who get learning through video get an average score of 84.28 while those who use torso are 82.22. Similarly, based on the improvement data, that video can improve student learning outcomes by 24.21 points, while torso increases learning outcomes by 22.84. There are differences in Biology learning outcomes between students who have high initial abilities and students who have low initial abilities. Students with low initial abilities are mostly able to achieve high learning outcomes, while students with high initial abilities can still maintain their learning outcomes in the high score category.